دور المؤسسات الوقفية التعليمية في التعليم : دراسة ميدانية تحليلية لنموذج إمارة دبي - مدحاني، عبد الله علي محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study to shed light on the role of Waqf institutions in education and to measure the efficiency of such role through governance and provision of qualitative education. Moreover, this study aims to highlight the importance of Waqf, its developmental and cultural role in Islamic history and modern age. The study also explicates the concept of Waqf & Endowments Law in Dubai and a comparative analysis with Waqf laws in Kuwait, Oman, UAE Federal Waqf Law, developmental role of Waqf Institutions in the Emirate of Dubai and analysis of such role in supporting education through the model of Arabic & Islamic Studies College. Doing so, this study has been divided into four sections the first section deals with the introduction and layout of the study the second section encapsulates the importance, legitimacy, governance and development of Waqf. The section also highlights the cultural role of waqf in Classical era and modern age of Islamic history. Section three deals with Dubai experience in the application of Waqf & Endowments Law in comparison with other state laws within the region as well as addressing the institutional governance system in the emirate of Dubai and the governance of Waqf institutions in Dubai; the fourth section deals with the developmental role of Waqf institutions in the Emirate of Dubai and its impact on education through the Arabic & Islamic Studies College model schools. In conclusion, the researcher relied on the inductive approach for collection of the scientific materials from the related theoretical and field sources. The study employs descriptive and analytical approach to highlight and analyze Dubai Waqf institutional experiences for the development and support of education. The study used quantitative approach to design and conduct surveys with selected respondents in the research sample. The finding suggests the presence of positive experience in Dubai waqf institutions towards the development of education sector of the state. The study suggests other sustainable steps towards improving the experiences for the benefit of the Muslim world